2016
DOI: 10.1111/jpn.12501
|View full text |Cite
|
Sign up to set email alerts
|

Effects of multistrain probiotics on growth performance, nutrient digestibility, blood profiles, faecal microbial shedding, faecal score and noxious gas emission in weaning pigs

Abstract: This experiment was conducted to investigate the efficacy of multistrain probiotics in weaning pigs. A total of 125 28-day-old weaning pigs [(Landrace × Yorkshire) × Duroc] with an initial average body weight (BW) of 7.26 ± 0.76 kg were randomly allotted into 5 treatments, 5 replicate pens/treatment with 5 pigs/pen for 42-day experiment. Dietary treatments were as follows: CON, basal diet; PC1, CON + 0.01% multistrain probiotics; PC2, CON + 0.03% multistrain probiotics; PC3, CON + 0.06% multistrain probiotics;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 40 publications
8
35
0
Order By: Relevance
“…In agreement with the current study, Yan and Kim (2013) and Lan et al (2016) reported that faecal Lactobacillus increased by probiotics supplementation. However, Lan et al (2016) observed a reduction in faecal E. Coli in weaning pigs fed probiotic blend. The findings of the current study confirm that the presence of Lactobacillus in the gastrointestinal tract is positively related to gut health and that the present probiotic blend (SLAB51) could be used as a good probiotic in growing-finishing pigs.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…In agreement with the current study, Yan and Kim (2013) and Lan et al (2016) reported that faecal Lactobacillus increased by probiotics supplementation. However, Lan et al (2016) observed a reduction in faecal E. Coli in weaning pigs fed probiotic blend. The findings of the current study confirm that the presence of Lactobacillus in the gastrointestinal tract is positively related to gut health and that the present probiotic blend (SLAB51) could be used as a good probiotic in growing-finishing pigs.…”
Section: Resultssupporting
confidence: 80%
“…Thus, dietary supplementation of probiotics indicated few or no significant evidence on pig blood characteristics. In agreement with the current findings, Chen et al (2005), Meng et al (2010), and Lan et al (2016) stated that feeding a probiotic blend to pigs did not influence blood traits. Conversely, it was found that probiotics supplementation in pigs determined an improvement of red blood cells .…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…However, the results are not always consistent. Lan et al . reported that supplementation with Bacillus ‐based multi‐microbe probiotic increased faecal Lactobacillus and decreased faecal E. coli counts in weaning pigs.…”
Section: Discussionmentioning
confidence: 99%